'It's Quite Stylish': Representations of American English and American Culture in English-Training Milieus in Delhi, India. (June 2014) - Proctor, Lavanya Murali
<x content-type="archive" xml:space="preserve">Abstract</x> English-training institutes seem to be ubiquitous in India, and they often index the United States through reference to 'American accent' training, American teachers, or simply American flags on their storefront signs. Against the broader backdrop of globalization, and through an examination of institute signs and advertisements and interviews with institute students and teachers, I show how 'America' is represented, produced, and consumed as a symbolic and cultural category within the cultural domain of English-training institutes.